Look up! Stratification and vertical approach to auditory prey cues in frog-biting midges (Corethrellidae) - Eltz, Thomas; Kimm, Hannah Luisa; Böddicker, Roger; Sigl, Maximilian; Meier, Rudolf; Virgo, Jonas (Frontiers in Ecology and Evolution, 2025)
Frog-biting midges (Corethrellidae) are tropical, blood-sucking micro-predators of frogs that locate their prey by eavesdropping on anuran mating calls. In the present study we used acoustic traps broadcasting the call of Savage’s Thin-toed Frog (Leptodactylus savagei) to elucidate frog-biting midge stratification in the rainforest as well as the directionality and spatial scale of their phonotactic approach. In an Amazonian rainforest in Ecuador, midges were attracted to acoustic traps in all forest strata, including the canopy of an emergent tree 38 m above the forest floor, with a significant effect of stratum on midge species composition. Of the eight putative species (MOTUs) of Corethrella delimited using COI barcoding (N = 158) four were also found in the highest forest stratum (28.5–38 m), with one of them showing a preference for the middle and top canopy. In both Ecuador and Costa Rica catch numbers of ground-based traps differed strongly depending on the orientation of an attached mesh tunnel (65 cm) that was used to filter approach directions. Very few midges entered traps when mesh tunnels allowed horizontal (0°) or inclined (45°) approach vectors, while the highest catch numbers were recorded when tunnels were oriented vertically (90°). Consistent results were obtained when the length of the attached tunnel was extended to 250 cm, confirming that the primary approach to a calling host follows a vertical trajectory, and demonstrating that frog-biting midges can perceive acoustic stimuli in the acoustical far field. When stimulus intensity was varied, midges showed a significant phonotactic response at sound pressure levels as low as 56 dBA at tunnel entrance (65 cm), equivalent to a male Leptodactylus savagei calling from ~30 m distance. Our results emphasize that, despite their minute size, frog-biting midges are highly sensitive to acoustic stimuli. They are also highly mobile, occupy all strata of the neotropical rainforests and preferentially home in on their prey from above.